A legal review of Section 121A of the Malaysian Penal Code: a proposed move towards amending the mandatory sentence of death / Anisa Fadhillah Mohamed Jamel … [et al.] - Mohamed Jamel, Anisa Fadhillah; Zahri, Nor Afiqah; Che Yusoff, Nur Farihah Izazi; Harun, Syahril Anuar (2014)
This research mainly concerns the mandatory death punishment a treason act under Section 121A of the Penal Code for Offences against the YDPA and the Rulers. The purpose of the study is to propose a discretionary punishment of death under the section as oppose to mandatory. The change in treason law and its penalties in the United Kingdom and Canada is also analysed and discussed together with the situation in Malaysia. This study highlights other issues of section 121A which are the vagueness of the section itself, unavailability of guidelines in sentencing and the redundancy of the law. This study is important to protect the life of the offenders as well as to promote fair, just and equal sentencing.